Orzecznictwo sądów amerykańskich w sprawach niewolnictwa – pomiędzy formalizmem a subwersją - Zajadło, Jerzy (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2014)
Article discusses a dilemma of judge facing a possibility (or necessity) of applying judicial disobedience. From the philosophical as well as theoretical point of view, the most intriguing would be an instance of judicial disobedience when applied to a state of democracy and the rule of law. In order to (re-)construct such an instance, the article traces the reader back to the middle of the 19th Century, when the moral conscience of (at least) some of American judges drove them to searching for the sound justification of judicial disobedience when faced with problem of slavery.
American courts adjudication concerning slavery – between formalism and subversion
Keywords: conflict between law and the moral conscience of judges; judicial disobedience